Physiological Apoptotic Agents have Different Effects upon Human Amnion Epithelial and Mesenchymal Cells - Moore, R.M; Silver, R.J; Moore, J.J (Placenta (Eastbourne), 2003)
Foetal membrane rupture is thought to follow from gene-controlled tissue remodelling and apoptosis. We reported previously that staurosporine, cycloheximide, actinomycin D, as well as more physiological apoptotic agents (lactosylceramide, 15d-PGJ2) increase prostaglandin release in parallel with induction of apoptosis in WISH and amnion epithelial cells. Also, inhibition of prostaglandin release by cyclooxygenase inhibitors or PKA activators is accompanied by a parallel decrease in apoptosis. We hypothesize that amnion prostaglandin metabolism is linked with apoptosis in amnion epithelial cells and thus to membrane rupture. Amnion mesenchymal cells are also critical for membrane integrity. Their susceptibility to apoptotic agents is unknown and is the subject of this report. In amnion epithelial cells, lactosylceramide (125μm) induced 6.5-fold, 20-fold increases in PGE2 and NMP production (apoptosis), respectively. Conversely, in mesenchymal cells, lactosylceramide doses up to 200μm had no effect on PGE2 or NMP release. In both cell types, incubation with 15d-PGJ2 (5–100μm) demonstrated dose and time dependent increases in PGE2 and NMP. PKA activators inhibited 15d-PGJ2 induced PGE2 release and apoptotis in epithelial cells, but not in mesenchymal cells, however. Major amnion cell types have different sensitivities to physiological apoptotic agents. Prostaglandin release occurs coincident with apoptosis in both amnion epithelial and mesenchymal cells.